The Mediation Role of Moral Personality Between Childhood Psychological Abuse and Cyberbullying Perpetration Attitudes of College Students - Zhang, Hang; Sun, Xiaohua; Chen, Liang; Yang, Hongze; Wang, Yandong (Frontiers in Psychology, 2020)
Guided by Social Learning Theory and General Aggression Model, this work aims to explore the impact of childhood psychological abuse on cyberbullying perpetration attitudes of college students and the mediating role of moral personality. Using stratified cluster random sampling method, 527 college students were tested by using the Childhood Psychological Abuse Scale, Moral Personality Adjective Evaluation Questionnaire for College Students, and the revised Chinese version of Cyberbullying Attitude Questionnaire. Results: (1) Childhood psychological abuse was significantly positively correlated with cyberbullying perpetration attitudes and showed a significant negative correlation with positive moral personality traits. (2) Positive moral personality traits had a significant negative correlation with cyberbullying perpetration attitudes. (3) Positive moral personality traits had a significant mediating effect between childhood psychological abuse and cyberbullying attitudes of college students. The mediating effect accounted for 11.11% of the total effect.